Wave propagation in a waveguide with continuous right-angled corners: Numerical simulations and experiment measurements. (March 2016) - Yu, Wuzhou; Wang, Xu; Wu, Rui; Yu, Jiangling; Jiang, Zaixiu; Mao, Dongxing
Abstract: This paper studied the acoustic wave propagation in a waveguide with continuous right-angled corners, with emphasis on the effect brought by the distance between the corners. The numerical analyses showed that at middle to high frequencies, the transmission loss ( TL ) of a multi-cornered waveguide was 2–5 dB higher than that of single-cornered and varied with frequency. To explain the performance at peaks and dips in the TL curve, analyses on eigenmodes and sound intensity distribution were conducted. The performance of multi-cornered waveguides was experimentally investigated, which fit well with the numerical results. The present study indicates that, for a waveguide with continuous corners, its acoustic performance is not simply a "summation" of two individual single-cornered ones. Both the standing wave modes and the evanescent modes between the corners lead to its complicated frequency performance.